Dietary Silicon Intake of Korean Young Adult Males and Its Relation to their Bone Status - Choi, Mi-Kyeong; Kim, Mi-Hyun (Biological trace element research, 2017)
Accumulated data suggests a positive effect of silicon on bone health; however, limited research exists on the silicon content of foods. To further the understanding of the relationship between dietary silicon intake and bone health, a food composition database of commonly consumed foods in Korea is required. For quantitative data on the intake levels of silicon, we analyzed the silicon content of 365 food items commonly consumed in Korea using inductively coupled plasma—atomic emission spectrometry following microwave-assisted digestion. To investigate the dietary silicon intake status and to examine the potential role of dietary silicon intake in the bone status of men, a total of 400 healthy Korean adult males aged 19–25 were observed for their diet intake and calcaneus bone density using the 24-h recall method and quantitative ultrasound, respectively. Clinical markers reflecting bone metabolism such as serum total alkaline phosphatase, N-mid osteocalcin, and type 1 collagen C-terminal telopeptide concentrations were also analyzed. Silicon intake of the subjects was estimated as 37.5 ± 22.2 mg/day. Major food sources of dietary silicon in the Korean male were cereal and cereal products (25.6 % of total silicon intake), vegetables (22.7 %), beverages and liquors (21.2 %), and milk and milk products (7.0 %). Silicon intake correlated positively with age, weight, energy intake, protein intake, calcium intake, and alcohol intake. After adjusted for age, weight, energy intake, protein intake, calcium intake, alcohol intake, smoking cigarettes, and regular exercise status, daily total silicon intake had no correlation with calcaneus bone density and the bone metabolism markers, but silicon intake from vegetables had a positive correlation with serum total alkaline phosphatase activity, a bone formation maker. These findings show the possible positive relationship between dietary silicon intake from vegetables and the bone formation of young adult males. Further investigation in a larger (Korean) population and correcting for additional nutritional confounders is required to confirm these findings.